MEMPRODUKSI TEKS PROSEDUR KOMPLEKS MENGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA SMA - Marhayanti, Ai (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
The background of this research is about the low of study result because students’s learning activity so low and the students’ not familiar with scientific method. The focus of this reasearch is made procedure komplex text with audio-visual media. This media is a way how to increase the students’ ability in producing  complex procedure in a good text. The method used in this research is qualitative-descriptive method. The kind of this research is classroom action research which was conducted in three cycles. The subject of this research is SMA Negeri 4 Pontianak. The object research is the visual-audio media . The research instrument  used is the test of study and also the observation sheet for observation the learning activity of the students and researcher. The results shows the medium of video could improve the writing skill complex procedure text, and the students’ attitude havea good invroved.